The Changing Nature of Gender Selection into Employment: Europe over the Great Recession - Juan J. Dolado; Cecilia García-Pe\~nalosa; Linas Tarasonis (Institute of Labor Economics (IZA), 2017)
The aim of this paper is to evaluate the role played by selectivity issues induced by nonemployment in explaining gender wage gap patterns in the EU since the onset of the Great Recession. We show that male selection into the labour market, traditionally disregarded, has increased. This is particularly the case in peripheral EU countries, where dramatic drops in male unskilled jobs have taken place during the crisis. As regards female selection, traditionally positive, we document mixed findings. While it has declined in some countries, as a result of increasing female LFP due to an added-worker effect, it has become even more positive in other countries. This is due to adverse labour demand shifts in industries which are intensive in temporary work where women are over-represented. These adverse shifts may have more than offset the rise in unskilled female labour supply.
Keywords: J31; 330; sample selection; gender wage gaps; gender employment gaps